A discriminant function for qualification of zebu semen samples before freezing - Casagrande, João Floriano; Silva, Roberto Gomes da; Mies Filho, Antonio (Pesquisa Agropecuaria Brasileira, 2014)
A discriminant function is presented for the selection of semen ejaculates from Zebu bulls before dilution and freezing. The estimated function was L= 100+ + 0.248 X1 - 0.237 X2 - 0.142 X3, where X1 is the percent initial motility, X2 the proportion of primary abnormalities, and X3 the proportion of secondary abnormalities, these variables being previously submitted to an arc-sin transformation. The above function was tested in terms of the probability of misclassification of any ejaculate and is considered suitable for practical use.